Dzieci rynku... Rynek dzieci... Osoby czy zasoby? - Michalski, Michał A. (Annales. Etyka w Życiu Gospodarczym, 2012)
The status of the child in the context of contemporary socio-cultural processes that are reflected in the market is the main issue discussed in this paper. It may be surprising to concentrate on children and the market, while the sphere of economic exchange is the scene of such actions as work, production and consumption which seem to be reserved to adult members of the society. Although there are issues – such as kids advertisement and its consequences, and children’s participation in the process of buying – that are discussed, the range of problems that deserve consideration is far wider. The questions analyzed in this paper concentrate on two aspects. First of them is the influence of the market sphere on the life of children as members of the families and the society. The question that should be asked here is whether a child can and should be regarded as any other consumer, or should be protected – e.g. against controversial marketing practices. The second group of problems is connected with the objective way of treating children which leads to formation of something that can be called the markets of children”. Both these sets of issues are the stimulus to analyze the way of understanding a child and its status in the society. It is also done through taking into consideration such issues as current concepts of socialization, antipedagogy, infantilisation and adultisation that influence and shape market processes. Finally the analysis undertaken in this paper leads to an attempt to answer the question whether in the current context children are seen as persons or resources.